Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Q-Cardsox terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas VII - Sulaiman, Alfin; Rahmawati, Fadhilah; Pradanti, Paskalia (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The low ability to understand mathematical concepts among SMPN 4 Magelang students is caused by the model and media used in learning. The purpose of this study is to analyze student learning completeness and determine which learning model is better between the Teams Games Tournament (TGT) model assisted by Q-Cardsox media and the direct learning model based on students' mathematical concept comprehension abilities. This research is a quantitative approach with a quasi-experimental type of research and uses a post-test only control group design. Samples were taken using the cluster random sampling technique, resulting in VII C as the experimental class and VII F as the control class, each consisting of 30 students. The research results show that the students' ability to understand mathematical concepts taught using the direct learning model did not achieve classical completeness. Meanwhile, those taught using the Teams Games Tournament (TGT) model assisted by Q-Cardsox achieved classical completeness. The ability to understand mathematical concepts of students taught with the Teams Games Tournament (TGT) model assisted by Q-Cardsox is better than the ability to understand concepts of students taught with the direct learning model.